PEMAHAMAN MAHASISWA ATAS METODE PENELITIAN KUALITATIF: SEBUAH REFLEKSI ARTIKEL HASIL PENELITIAN - Sari Pertiwi, Widya Hanum; Weganofa, Riza (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2015)
This article aimed at describing students’ difficulties in writing research-based paper. It is expected that lecturers who teach research methodology course will get a lot of benefit from this study. The respondents of this research was 131 students who conducted a research which employed qualitative design and wrote their articles which showed the research results. The data gained showed that the university students’ who became the respondents had difficulties in writing research-based article related toqualitative research design. The difficulties were: most of the students showed their difficulties in identifying the research instrument, data sources, and relevant sources that support their research. Next, they were also had obstacle in explaining or discussing the result of their research. It means that they did not understand that qualitative researchdesign employs snowballing technique and enabling the researcher to generate theory.